What matters for environmental concerns among university students in Bangladesh? An empirical study - Saha, Bijoya; Ahmed, Mufti Nadimul Quamar; Ahmed, Khandaker Jafor; Atiqul Haq, Shah Md (Frontiers in Climate, 2025)
IntroductionExperts have a well-established consensus regarding the detrimental effects of human activities on the environment, including extreme temperature events, rainfall variability, pollution, deforestation, biodiversity loss, and flood occurrences—all of which significantly stress Earth’s natural systems. This study investigates the level of environmental concern among university students in Bangladesh, considering their socio-demographic factors.MethodsA comprehensive survey was conducted using a self-administered questionnaire targeting 380 final-year bachelor and master’s students from various academic disciplines at Shahjalal University of Science and Technology (SUST) Sylhet, Bangladesh. The analysis involved variables such as gender, completion of university courses related to the environment or climate change, disciplinary background, and vulnerability to climate change or extreme weather events in their home locality. Relationships between these variables and the students’ environmental concerns were examined using cross-tabulation with the Chi-square test and mean difference with the ANOVA test.ResultsThe findings indicate a high level of knowledge and significant concern among students regarding environmental issues, with disciplinary background being the primary determinant of environmental concern level. Additionally, completing university courses on environmental or climate change topics and experiencing vulnerability to such events in one’s hometown are significant predictors of environmental concerns.DiscussionThis study highlights the growing environmental concerns among university students and underscores the need for further scientific research to comprehensively understand their impact on population dynamics.